Recreational use of the Black Sea coast of Russia in Krasnodar Krai: significance and sensitivity of natural complexes - Volkova, Tatiana; Goretskiy, Vladislav; Klimov, Nikon; Rudenko, Ilya; Nagalevsky, Eduard (Anais Brasileiros de Estudos Turísticos, 2022)
The paper presents the results of a study of the current condition and prospects of development of sustainable tourism in the coastal zones of the Black Sea in Krasnodar Krai (Russia). The aim of the study is to give a basis for and develop a method for determining the level of recreational pressure on coastal zones. The research methods applied are the empirical and practical methods of comparison and systemic and comprehensive analysis. The analysis based on statistical techiniques establishes the primary indicators for assessing the sustainability of tourism development in coastal areas. The conclusions confirm that the establishment of protected natural areas and the promotion of environmentally responsible practices among tourists and local residents are necessary to conserve the natural heritage of the region.